2018
DOI: 10.3389/fimmu.2018.00927
|View full text |Cite
|
Sign up to set email alerts
|

Automated Processing and Evaluation of Anti-Nuclear Antibody Indirect Immunofluorescence Testing

Abstract: Indirect immunofluorescence (IIF) is considered by the American College of Rheumatology (ACR) and the international consensus on ANA patterns (ICAP) the gold standard for the screening of anti-nuclear antibodies (ANA). As conventional IIF is labor intensive, time-consuming, subjective, and poorly standardized, there have been ongoing efforts to improve the standardization of reagents and to develop automated platforms for assay incubation, microscopy, and evaluation. In this study, the workflow and performance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 59 publications
2
13
0
Order By: Relevance
“…Considering results within ± one titer difference as acceptable, the overall agreement between automated and classical endpoint titer was 75.9% (Table 6), consistent with previous studies (23,24,29). For samples with the same single patterns by both Helios and visual readings (Table 7), the overall error rate was 26.0%, similar to previous reports (25,29,37,38). The high error rates may be due to the single-well titration method that most automated systems currently use.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Considering results within ± one titer difference as acceptable, the overall agreement between automated and classical endpoint titer was 75.9% (Table 6), consistent with previous studies (23,24,29). For samples with the same single patterns by both Helios and visual readings (Table 7), the overall error rate was 26.0%, similar to previous reports (25,29,37,38). The high error rates may be due to the single-well titration method that most automated systems currently use.…”
Section: Discussionsupporting
confidence: 89%
“…The high error rates may be due to the single-well titration method that most automated systems currently use. Won suggested the multi-well (2 or 3 wells) based line slope titration method to improve the accuracy (37). Moreover, our analysis on pattern dependency of automated endpoint titer prediction demonstrated that Helios predicted higher titers for homogeneous patterns but lower titers for speckled patterns, consistent with a previous study (37).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…cancer, infection) or in healthy individuals [1,[16][17][18], the test can have low specificity for CTD. Furthermore, IIF is a labour-intensive technique that requires highly skilled laboratory technicians to interpret the result and is therefore subject to high inter-observer variability [19][20][21]. Solid-phase immunoassays (IAs) offer an alternative to IIF.…”
Section: Introductionmentioning
confidence: 99%
“…2019) , immunofluorescence assay (IFA) (Ricchiuti et al . 2018) and the haemagglutination‐haemagglutination inhibition (HA‐HI) method (Peng et al . 2007; Chaka et al .…”
Section: Introductionmentioning
confidence: 99%